PERBANDINGAN PROFIL DISTRIBUSI VERTIKAL 137Cs DI LAPISAN TANAH HASIL PENGUKURAN TERHADAP SIMULASI - Suhartini, Nita (Makara Journal of Science, 2006)
Comparison Of 137Cs Vertical Distribution Profile At Soil Layer Obtained By Measurement And Simulation. This investigation aimed to compare a profile of 137Cs vertical distribution at soil layer in the stable site (undisturbed site). Conservation forest that has been becoming as conservation area since 1925 namely Gn. Pangrango was selected as study site. Sampling of soil was done in Pancawati – Ciawi. Sampling was done by using scrapper ( 20 x 50) cm, with layer increment of 2 cm until the depth of 24 cm (107 kg/m2) or 26 cm (137 kg/m2), and sampling was done at 5 points. Soil samples were brought to the laboratory for preparation and analysis of 137Cs content by using MCA at 662 keV energy. The result showed that the comparison of 137Cs vertical distribution profile between measurement and simulation has a significant differences.